Cost-effectiveness of sorafenib for treatment of radioactive iodine (rai)-refractory locally advanced/metastatic differentiated thyroid cancer (dtc) in Turkey - Erdal, E.; Sayman, Haluk; Türkmen, Cüneyt; Aral, Ferihan; Yıldız, Özcan; Okutur, Kerm; Paralı, E.; Değer, C.; Tunalıoğlu, A.; Sar, Christina; Asan, Simona; Sümer, Fulya Erendağ; et al. (Elsevier Science, 2015)
OBJECTIVES: Sorafenib is the first product approved for treatment of RAI refractory locally advanced/metastatic DTC patients. This study was conducted in order to analyze cost-effectiveness of sorafenib for treatment of patients with RAI refractory locally advanced/metastatic DTC in Turkey. METHODS: A cohort partition model assigning patients to one of three health states according to the proportion of patients who are progression-free, progressed, or dead in each 28-days cycle was adapted to Turkish setting. The incremental cost-effectiveness ratios (ICER) were calculated per quality-adjusted life years (QALYs) and life-years (LYs) gained. Turkish payer’s perspective was taken and time-horizon was set as patient’s lifetime (maximum 30 years). Sorafenib was compared to the best supportive care (BSC) within the model since there are no agents for treatment of patients on this stage of the disease. Essential clinical inputs were derived from DECISION trial and local resource-utilization data were based on expert opinions through an expert panel. Sensitivity of the results was evaluated in terms of key inputs by deterministic oneway and probabilistic sensitivity analyses. All costs were calculated in Turkish Liras (TL) and converted to USD using TL/USD currency rate as 2.2 (mid-2014). RESULTS: Total cost of sorafenib-treated patients is 24,384 USD higher compared to BSC. Besides, sorafenib is associated with increments of 1.29 LYs and 0.80 QALYs compared to BSC. The ICER of sorafenib per LYs and QALYs gained compared to BSC were determined as 18,851 USD and 30,485 USD respectively. One-way sensitivity analysis demonstrated that results are not sensitive to the changes in model inputs and pharmacoeconomic analysis results were validated by probabilistic sensitivity analysis. CONCLUSIONS: Sorafenib is cost-effective for treatment of patients with RAI refractory locally advanced/metastatic DTC compared to BSC with an ICER value below the willingness-to-pay threshold (3-times GDP per capita ? 32,346 USD) for Turkey.
WOS: 000354498503198
Keywords: Sorafenib; Refractory